The Care Leavers’ Annual Lecture 2016 - Jimmy Paul (Scottish Journal of Residential Child Care)
A care experienced person is invited to host the Who Cares? Scotland Care Leavers Annual Lecture, and this is the transcript of the lecture from 2016. Jimmy Paul, an alumni member of Who Cares? Scotland, shares his story and makes several compelling points in doing so. With the announcement of the root and branch review of care and the pledge to listen to 1000 care experienced voices, Jimmy explains that we have a unique opportunity to transform care experiences across Scotland, and even globally. He argues that we need to challenge the stigma that children face by triangulating; presenting more stories and qualitative richness to help people understand the damning statistics and outcomes of care leavers. Children need to feel claimed and loved by people around them, and it is vital that the care system doesn’t repeat the trauma of their earlier lives. Ongoing, nuanced debates about what does (and doesn’t) work across the care system is vital to an improved care system.